2013
DOI: 10.1371/journal.pone.0072259
|View full text |Cite
|
Sign up to set email alerts
|

Self-Fulfilling Prophecies as a Link between Men’s Facial Width-to-Height Ratio and Behavior

Abstract: The facial width-to-height ratio (fWHR) has been identified as a reliable predictor of men’s behavior, with researchers focusing on evolutionary selection pressures as the underlying mechanism explaining these relationships. In this paper, we complement this approach and examine the extent to which social processes also determine the extent to which men’s fWHR serves as a behavioral cue. Specifically, we propose that observers’ treatment of target men based on the targets’ fWHR subsequently affects behavior, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
2
57
1
Order By: Relevance
“…There are also as many as seven alternative hypotheses that have been presented to explain the fWHR association with T (see research and discussion by Haselhuhn et al, 2013; Hehman et al, 2015; Whitehouse et al, 2015; Zebrowitz et al, 2015; Eisenbruch et al, 2017; Kramer, 2017). One hypothesis that has been under-examined thus far is that the fWHR-behavior relationships are a byproduct of the association between fWHR and other relevant traits.…”
Section: Discussionmentioning
confidence: 99%
“…There are also as many as seven alternative hypotheses that have been presented to explain the fWHR association with T (see research and discussion by Haselhuhn et al, 2013; Hehman et al, 2015; Whitehouse et al, 2015; Zebrowitz et al, 2015; Eisenbruch et al, 2017; Kramer, 2017). One hypothesis that has been under-examined thus far is that the fWHR-behavior relationships are a byproduct of the association between fWHR and other relevant traits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research reveals that the positive relationship between FWHR and aggression is moderated by objective and subjective measures of social status, with a significant relationship only for men with relatively low status (Goetz, Shattuck, Miller, Campbell, Lozoya, Weisfeld, & Carre, 2013). There is also evidence that self-fulfilling prophecy effects may contribute to less pro-social behavior in men with a higher FWHR (Haselhuhn, Wong, & Ormiston, 2013). Furthermore, sex-role socialization may contribute to the fact that, with one exception (Lefevre, Etchells, Howell, Clark, & Penton-Voak, 2014), a relationship between FWHR or babyfaceness and aggressive or assertive behavior is more reliable for men than women (Carre & McCormick, 2008; Geniole, Keyes, Carre, & McCormick, 2014; Mileva et al, 2014; Zebrowitz et al, 1998), with these results leading many researchers to study only men.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that FWHR is related to personality judgments made by others (e.g., Carré et al 2009;Haselhuhn, Wong, and Ormiston, 2013;Stirrat and Perrett 2010) thus it is plausible that a referee's judgment could have been influenced by this bias. However, this argument does not apply to the relationship found between FWHR and goals scored since referee judgment is minimally involved.…”
Section: Discussionmentioning
confidence: 99%